2019
DOI: 10.3390/molecules24173189
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Composition and Nutritional Profile of Rainbow Trout (Oncorhynchus mykiss) Heads and Skipjack tuna (Katsuwonus Pelamis) Heads

Abstract: In order to evaluate the application potential of rainbow trout (Oncorhynchus mykiss) heads and skipjack tuna (Katsuwonus pelamis) heads; proximate composition, amino acids, fatty acids, carnosine, and anserine contents were analyzed in this study. Rainbow trout heads showed significantly higher protein (29.31 g/100 g FW, FW is abbreviation of fresh weight) and lipid (6.03 g/100 g FW) contents than skipjack tuna heads (18.47 g/100 g FW protein and 4.83 g/100 g FW lipid) (p < 0.05). Rainbow trout heads and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 36 publications
7
10
1
Order By: Relevance
“…RRM-CON contained 14.3% protein, 58.4 % water, 4.5 % ash and 20.1 % lipid. These results differ significantly from those found by Li et al. (2019) .…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…RRM-CON contained 14.3% protein, 58.4 % water, 4.5 % ash and 20.1 % lipid. These results differ significantly from those found by Li et al. (2019) .…”
Section: Resultscontrasting
confidence: 99%
“…The most abundant amino acids were Glutamic acid (14.0-14.6%), Aspartic acid (10.02-10.2%), Alanine (9.65-10.2%), Lysine (7.35-8.08%), Leucine (7.02-7.79%) and Serine (5.98-6.24%). These results are in the same range as Li et al (2019) found in heads of rainbow trout. Glycine and arginine are merged in our method and have a content of 19.8-20.7% of the total amino acids in our study.…”
Section: Amino Acid Compositionsupporting
confidence: 89%
See 1 more Smart Citation
“…Considering the fact that even in the same species, the HCD contents differ according to the part of the animal, the process model of the sample, and the sex, age, and genotype of the specimen [ 13 ], the difference in the HCD contents in chicken breast between this work and other reports is acceptable. In addition, our results for tuna ( Thunnus tonggol and Katsuwonus pelamis ) and trout ( Oncorhynchus aguabonita ) are also in the range of values obtained in previous studies [ 2 , [14] , [15] , [16] ], indicating the reliability of the method for the quantification of HCDs in this study and the greater abundance of HCDs in migratory fishes [ 14 ].…”
Section: Resultssupporting
confidence: 85%
“…These by-products are rich of macro -and micronutrients and their use can result in the production of fishmeal and fish oil to use in animal nutrition. Nevertheless, these products are still underused (Olsen et al 2014) resulting in economic and environmental issues (Li et al 2019). The FAO estimated discards from the world's fisheries to exceed 20 Mt/year and recommended reconsidering their use (FAOSTAT 2014).…”
Section: By-products Deriving From Fishery and Aquaculturementioning
confidence: 99%